Tachycardia-bradycardia syndrome in a patient with atrial fibrillation: a case report - Choi, Sung Hwan; Choi, Sung Lark; Lee, Bong Yeong; Jeong, Mi Ae (Korean journal of anesthesiology, 2015)
An 83-year-old woman was scheduled for a second transurethral resection of a bladder tumor. The preoperative electrocardiogram evaluation revealed atrial fibrillation with a slow ventricular response (ventricular rate: 59 /min). After intravenous injection of 1% lidocaine 40 mg and propofol 60 mg, the ventricular rate increased to 113 beats/min and then fell rapidly to 27 beats/min. Blood pressure was 70/40 mmHg. Later an atrial fibrillation rhythm, with a ventricular rate of 100-130 beats/min, was observed together with a sinus pause and sinus rhythm with a ventricular rate of 40-50 beats/min. An external pacemaker was applied and set at 60 mA, 40 counts. After the patient regained consciousness, she presented an alert mental state and had no chest symptoms. She was discharged 2 weeks later without complications after insertion of a permanent pacemaker.